Efeito antitumoral do ácido graxo docosahexaenóico em células de glioblastoma humano - Queiroz, Fernanda de Oliveira [UNIFESP] (2017)
Glioblastoma Multiforme is considered one of the most serious and common brain neoplasias, representing 50% of ali malignant tumors present in the brain. With a poor prognosis, half of the patients die within 1 year of diagnosis. Gliomas present great changes in their morphology, so they are considered tumors of high complexity. These morphological changes are one of the causes for resistance to existing therapies. In order to look for new alternatives for the treatment of these neoplasias, several compounds have been studied, among them, the fatty acids. Fatty acids are organic components, poorly soluble in water and play important roles in cell membranes and metabolic processes. They are divided into saturated and unsaturated. In order to understand the action of saturated fatty acids, palmitic acid and polyunsaturated fatty acids, docosahexaenoic acid (DHA) and arachidonic acid (AA) in head cancer, in this study we used glycoproteinoma multiforme cells from the T98G lineage. Different assays were performed to elucidate the mechanism of operation. Initially, cell viability tests were performed by MTT to observe whether these compounds cause death or the reduction of cell viability. In sequence, membrane fluidity tests were performed to understand the selectivity of DHA, since only this acid had a reduction in the viability of human glioblastoma cells. To understand and quantify the type of death, whether apoptotic or necrotic, flow cytometry and Co-incubation Hoechst 33342 / PI were performed at different concentrations and observed a higher AnexinN labeling in these cells. Nuclear morphological changes in T98G cells were observed from Hoechst .33342 cells. Data obtained showed fragmented, picnotic and condensed nuclei, which are characteristics of cellular apoptosis. Levels of reactive oxygen species were also performed. With the use of the DHE probe, we observed an increase in the production of reactive oxygen species (ROS), which indicates that the type of death we are observing is apoptosis. The viability of DHA is probably due to the induction of the production of high levels of ROS.